Indigenous goby population in Mandaluyong River system and its conservation by communities in Iligan City, Philippines (Journal of Environmental Science and Management, 2013)
Threats of water pollution, unregulated extraction of resources, and sprawling urbanization are some of the common issues of Mandulog River, a home for indigenous freshwater gobies.This study was conducted to assess the status of freshwater gobies and how the resident communities exert conservation efforts to the river and the inhabiting gobies. Standard method of collection of gobies was done. Interviews with semi-structured questionnaires were used to know the conservation measures of the residents. Ten goby species belonging to three families namely, Family Eleotridae (Belobranchus belobranchus), Giuris margaritacea, and Oxyeleotris lineolata, Famly Gobiidae (Awaous melanocephalus), Awaous ocellaris, Glossogobius celebius, Glossobius giuris. Periophthalmus barbarus and Sicyopterus lagocephalus, and Family Rhyacichthyidae (Rhyacichthys aspro), can be an alternative source of food and livelihood. They were caught by-catch, while employing some destructive fishing methods like cyanide fishing, electric fishing, and use of fine mesh nets. The awareness of the residents to the adverse impacts of water pollution, unregulated human activities, and destructive fishing had strengthened their conservation measures. A multi-stakeholder management approach is created through concerted proactive conservation measures like protection of the goby population, the river-riparian ecosystems, enhanced scientific information, and the legal intervention of the localgovernment.